Effects of the Ukrainian crisis in Transcarpathia: The Hungarian perspective - Ágnes Erőss; Katalin Kovály; Patrik Tátrai (University of Warsaw, Centre of Migration Research (CMR), 2016)
Ukraine's turbulent recent history has had serious economic and social effects in its westernmost region, Transcarpathia. The East Ukrainian armed conflict, accompanied by a serious economic downturn, resulted in major modifications in individual and family life strategies determined by emigration and the policies of the neighbouring V4 states. The main focus of the present research was to study how recent political events (Euromaidan, the Russian takeover in Crimea, the Donbas conflict) affected Transcarpathia and its ethnic Hungarian population; furthermore, how patterns of individual and family life and migration strategies have been influenced by Hungary's kin-state politics. The study is based on analysis of statistical data and policy documents, complemented by semi-structured interviews conducted in spring 2016. We found that the dynamics of emigration from Transcarpathia in the past few years are fuelled by the unrest in Eastern Ukraine (including the military drafts) and Hungary's kin-state politics, especially the preferential (re)naturalisation simplifying the acquisition of Hungarian citizenship. Individual and family livelihood strategies, migration patterns and cross-border connections are influenced by the regional geopolitics of V4 countries. We argue that the western neighbours of the weakening Ukraine have unobtrusively made attempts to take advantage of the changing geopolitical circumstances in order to increase their influence and attract human resources.
Keywords: 330; Transcarpathia; kin-state politics; migration; Hungary; cross-border relations; Ukraine crisis